2021
DOI: 10.1155/2021/7742894
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Performances of the European Blackbird (Turdus merula) in Morocco: Habitat Selection, Breeding Phenology, and Breeding Success

Abstract: The European Blackbird (Turdus merula) is a widespread species. In Morocco, available knowledge on this species is limited to a few descriptive pieces of information with no detailed data provided. With climate change and the intensification of agricultural activities, the study of the breeding performances of this species is indispensable for management purposes. This study investigates breeding biology, nesting habitats, breeding chronology, and reproductive success of the European Blackbird in both apple or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…Further, farmland and aquatic birds were the most investigated birds (Hanane and Baamal 2011;Hanane 2016;Mansouri et al 2018Mansouri et al , 2019Mansouri et al , 2020El Hassani et al 2021), while forest and Mountainous species have received little interest (Cherkaoui et al 2009;Hanane et al 2012;Mansouri et al 2021a). Therefore, the investigation of forest ecosystems is suggested to fill the gap in forest birds.…”
Section: Introductionmentioning
confidence: 99%
“…Further, farmland and aquatic birds were the most investigated birds (Hanane and Baamal 2011;Hanane 2016;Mansouri et al 2018Mansouri et al , 2019Mansouri et al , 2020El Hassani et al 2021), while forest and Mountainous species have received little interest (Cherkaoui et al 2009;Hanane et al 2012;Mansouri et al 2021a). Therefore, the investigation of forest ecosystems is suggested to fill the gap in forest birds.…”
Section: Introductionmentioning
confidence: 99%
“…orchards and cereals are suggested to infuence negatively the diversity of birds because of the reduction of breeding and foraging resources which are considered necessary elements for birds. In addition, the concentration of human habitations and the agricultural activities such as the use of pesticides in agricultural felds afect the abundance and diversity of many passerines such as Turdus merula and Serinus serinus [36,[74][75][76]. Tis study showed a seasonal variation of avian diversity between both valleys of the Central High Atlas, which was one of the neglected aspects of avian diversity studies in the High and Middle Atlas Mountains of Morocco, as well as in the entire North Africa [20,64,76].…”
Section: Discussionmentioning
confidence: 97%
“…This species richness is the result of the diversity of natural ecosystems (Dakki et al 2020;Fouzi et al 2020;Kusi et al 2020), climate circumstances (Tramblay et al 2012), and geographical situation (Mensour et al 2019). Regarding In Morocco, avian species are widely distributed in different ecosystems, counting forests, wetlands (Squalli et al 2022), farmlands (Mansouri et al 2020;El Hassani et al 2021), and urban areas (Douini et al 2022). However, most ornithological research was realised in lowlands, while in high altitudes, investigations are rare and fragmentary.…”
Section: Introductionmentioning
confidence: 99%